2009
DOI: 10.1136/emj.2008.061119
|View full text |Cite
|
Sign up to set email alerts
|

Can age-based estimates of weight be safely used when resuscitating children?

Abstract: Both length-based and age-based estimates of weight outperformed the currently accepted "gold standard" mathematical estimate when applied to children up to 11 years of age (approximately 35 kg). Length-based estimates were statistically superior, but the physical limitations and technical constraints posed when attempting to accurately measure a child's length in emergency environments may favour the simplicity of using the child's age against tables of growth chart reference data to provide an estimate of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 5 publications
0
18
0
3
Order By: Relevance
“…However, it may be difficult and unfair to expect parents to safely state their child's weight during resuscitation, and the study only used clinically stable children, excluding emergency cases 13. The use of growth charts to estimate weights by using the 50th centile has shown better accuracy than the current formula14 but, once again, requires the information to be readily available. Other formulae such as the mid-arm circumference or shoe size-based systems are available but not straightforward 15.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be difficult and unfair to expect parents to safely state their child's weight during resuscitation, and the study only used clinically stable children, excluding emergency cases 13. The use of growth charts to estimate weights by using the 50th centile has shown better accuracy than the current formula14 but, once again, requires the information to be readily available. Other formulae such as the mid-arm circumference or shoe size-based systems are available but not straightforward 15.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than use a formula at all, a standard growth chart of weight for age might be preferable 19 20. Firstly however, although growth charts are used in nonurgent settings, they are not always available in emergency situations.…”
Section: Discussionmentioning
confidence: 99%
“…The methods chosen to evaluate in our population were the APLS, Best Guess, Luscombe and Owens, Nelson's formula, and Argall's modification . The two length‐based methods used were Broselow® and Sandell® tapes, as well as the WHO standard reference growth charts . The study was approved by the Human Research Ethics Committee of NT Department of Health & Families and Menzies School of Health Research, and consent was not required as the data were pre‐existing and de‐identified for our research purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Data from such communities are still showing high rates of growth faltering in the first few years of life . A consideration of this has seen the NT adopt the World Health Organization (WHO) growth charts, and a recent study has also advocated using growth chart reference data to provide an estimate of weight in emergency situations . Programmes of growth monitoring and intervention occur in the NT through the Healthy Under Five Kids Data Collection or Growth Assessment and Action (GAA) Programme.…”
Section: Introductionmentioning
confidence: 99%